PERAN BUDAYA ORGANISASI, KOMUNIKASI, STRESS KERJA, DAN KOMPENSASI TERHADAP KINERJA PEGAWAI (STUDI PADA DINAS PERKEBUNAN PROV JATENG) (Students' Journal of Economic and Management, 2014)
This study analyzed the influence of organizational culture, communication, job stress and employee compensation to performance. The research object in this paper is the Plantation Office Prov. Sampling technique in this study is the use of data or entire employee population by using the method of data collection questionnaire (questionnaire) by distributing a list of statements to the respondents in order to obtain information. The purpose of the study was formulated to look for answers that affect employee performance. The data were analyzed using factor analysis to test the validity of the question items, Cronbach alpha to test the reliability of the instrument , regression analysis , to examine the influence of the partial of each independent variable was tested with the coefficient of determination ( R ² ) and F test model to test and prove partial effect of each independent variable. The results of the research are : ( 1 ) Compensation highest positive effect on employee performance, meaning high smakin compensation will lead to increased employee performance. ( 2 ) Organizational Culture has a positive effect on employee performance means both organizational culture that must be achieved to improve employee performance such as by encouraging employees to achieve optimal productivit. ( 3 ) Communication The third positive effect on employee performance means the better the communication will improve employee performance. ( 4 ) Work Stress lowest impact on employee performance this means that higher job stress will smakin to greater employee performance. Keywords : Organizational Culture, Communications, Job Stress, Compensation and Employee performance.